Security Governance: Mafia Control over Ordinary Crimes. (July 2020) - Aziani, Alberto; Favarin, Serena; Campedelli, Gian Maria
Objectives: This study tests whether mafias, as archetypical criminal organizations that exert control over local communities, protect their territories against ordinary criminality. Our hypothesis is that mafias have both the incentives and the capacities to supply security governance to specific territories. This is a distinctive feature of mafias that deserves to be considered. Method: To understand whether mafias' territorial control is associated with lower levels of ordinary criminality, we conduct a panel data analysis on 110 Italian provinces (2004 to 2015). System generalized method of moment and Driscoll–Kraay standard errors are performed to test our hypothesis. This study exploits an aggregated measure of thefts, robberies, and assaults as dependent variable. A standardized index derived from the number of active mafia groups in a province is our proxy of mafia control. Results: The article statistically shows that mafias limit ordinary criminality, whereas less stable and unstructured criminal groups do not. Conclusions: The results indicate that crime prevention and the maintenance of public order should be considered among the pillars of mafia's governance. By controlling and reducing ordinary crimes, mafias overcome the role of law enforcement and institutional justice increasing consensus among the population. Consequently, the state may better contrast mafias by becoming a stronger supplier of security.